Bacterial community dynamics are linked to patterns of coral heat tolerance - Maren Ziegler (Nature Portfolio, 2017)
Coral-associated microbes could enhance the capacity of their host organism to respond to environmental change. Ziegler and colleagues use a reciprocal transplant experiment to show that microbiomes of heat-tolerant corals are more resilient to change than those of heat-sensitive corals.